Webinar series 1/2021 - adapting to new normal: technologies in teaching & learning / Sharifah Sheha Syed Aziz Baftim - Syed Aziz Baftim, Sharifah Sheha (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
The Academy of Language Studies APB) has organized its first International webinar titled "Adapting to New Normal: Technologies in Teaching & Learning" which was held on Wednesday, 3 March 2021 at UiTM Negeri Sembilan Kuala Pilah Campus. The Guest Speaker for the webinar was Associate Professor Dr Kumar Laxman from University of Auckland, with Ms Dzeelfa Zainal Abidin as the Moderator and Dr Rafidah Kamarudin as the Master of Ceremony. The one-hour webinar was held online through the use of Cisco Webex and APB Kuala Pilah Facebook channel. Associate Professor Dr Kumar Laxman specializes in instructional design and technology and he has worked in various capacities both as an educator and instructional designer with many reputable educational organizations and tertiary institutions. In the webinar, he touched on the different aspects of educational technologies, and shared research-based best practices in technology integration in curriculum and instruction. Dr Kumar also emphasized the importance of the ability of teachers to embed technology use into students' regular classroom work, as this is essential to the development of "technology literacy". He also discussed some principles to guide effective instructional practice as well as strategies to make learning meaningful.